Investigation of Effects of Cushioning Packaging on the Physiological and Quality Changes in Chinese Olive Fruits During Cold Chain Transportation - Han Lin; Fanghao Fu; Jinghai Li; Jiahui Liu; Kaiyang Du; Bingxia Zhu; Zhixiong Guo; Tengfei Pan; Wenqin She (Foods)
To gain a deeper understanding of the mechanisms by which cushioning packaging preserves the quality of Chinese olive fruits during cold chain transportation and extends their shelf life, this study simulated cold chain conditions and investigated the effects of cushioning packaging on the physiology, antioxidant capacity, and secondary metabolites of fruits during a 20-day shelf life. The results indicated that the decay rate in cushioning-packaging-treated fruit was 75% lower than that in the unbuffered packaging fruit at day 20 of shelf life. Simultaneously, cushioning packaging treatment mitigated the damage severity of the cell membrane structure and kept the cell membrane permeability at a low level, which was 15.34% lower than that in the unbuffered packaging fruit at day 20 of shelf life. Additionally, cushioning packaging effectively restrained the increases in malondialdehyde (MDA) content and alleviated the decline in chlorophyll and total flavonoid contents. It kept a balance among reactive oxygen species (ROS), antioxidant levels, and antioxidant enzyme activities, thereby reducing mechanical-damage-induced decay rates in Chinese olive fruits during the shelf life. Furthermore, metabolome analysis of Chinese olives during the shelf life was performed comparing those without buffered packaging to those with buffered packaging. The metabolome analysis found that the flavonoid biosynthetic pathway exhibited a higher accumulation of chrysin, neohesperidin, naringenin chalcone, sakuranetin, quercetin, catechin, and naringenin metabolites in cushion-packaging treatment compared to those without cushioning treatment. Furthermore, within the phenylalanine metabolic pathway, the accumulation of phenylalanine, p-coumaraldehyde, p-coumaric acid, coniferin and caffeoyl quinic acid metabolites was significantly higher in buffered-packaging groups compared to those without buffering. Together, these findings suggest that cushioning packaging can effectively sustain the integrity of cell membranes and enhance the shelf-life quality of Chinese olive fruits by regulating the balance of ROS and mitigating oxidative stress during cold chain transportation.